2021
DOI: 10.7759/cureus.12960
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Intraoperative Touch Imprint Cytology for the Diagnosis of Axillary Sentinel Lymph Node Metastasis of Breast Cancer: Comparison With Intraoperative Frozen Section Evaluation

Abstract: Introduction The intraoperative frozen section is a recommended method to detect breast cancer metastasis to axillary sentinel lymph nodes (SLNs); however, frozen section is not widely available and requires an experienced staff. Alternatively, touch imprint cytology (TIC) is a simple and cost-effective technique to detect metastasis. Therefore, in this study, we assessed the diagnostic accuracy of TIC for detecting SLN metastasis and compared it with intraoperative frozen section evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
5
7
0
Order By: Relevance
“…Fulltext reviews were performed and 16 were excluded for the following reasons: did not compare TIC and FSB (n = 10) and insufficient information to calculate TP/TN/FP/FN (n = 6). Finally, 14 studies were included in the metaanalysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Literature Searchmentioning
confidence: 99%
“…Fulltext reviews were performed and 16 were excluded for the following reasons: did not compare TIC and FSB (n = 10) and insufficient information to calculate TP/TN/FP/FN (n = 6). Finally, 14 studies were included in the metaanalysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Literature Searchmentioning
confidence: 99%
“…Touch imprints have been extensively used in the cytological evaluation of tumor cells in several types of cancer, including primary and metastatic breast cancer [ 20 , 21 ], melanoma [ 22 ], as well as hepatic malignancies [ 23 ]. Touch imprint iFC offers several advantages to assist clinical management.…”
Section: Resultsmentioning
confidence: 99%
“…Others such as Menes et al 18 have indicated that the sensitivity of touch preparation is comparable to that of FS and since touch preparation is more rapid and less expensive, uses less tissue, and does not create freezing artifacts, they concluded that touch preparation is the best available method for intraoperative evaluation of SLN. Newer studies also showed that IC is an effective and quick method for detecting macro‐metastasis in breast SLN 19,20 . One other limitation is that the documentation at the time of IOC was limited, and it was therefore impossible to accurately assess the adequacy of gross assessment as well as specimen sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Newer studies also showed that IC is an effective and quick method for detecting macro‐metastasis in breast SLN. 19 , 20 One other limitation is that the documentation at the time of IOC was limited, and it was therefore impossible to accurately assess the adequacy of gross assessment as well as specimen sampling. The main finding in our study indicate that a maximum of three slides or three blocks for microscopic examination did not impact the sensitivity of SLN IOC.…”
Section: Discussionmentioning
confidence: 99%